2022
DOI: 10.3390/pharmaceutics14030594
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibited ADAM10 Mediated CXCL16-Cleavage and T-Cells Recruitment to Pancreatic β-Cells in Type 1 Diabetes Mellitus in Mice

Abstract: Background: CXCL16 attracts T-cells to the site of inflammation after cleaving by A Disintegrin and Metalloproteinase (ADAM10). Aim: The current study explored the role of ADAM10/CXCL16/T-cell/NF-κB in the initiation of type 1 diabetes (T1D) with special reference to the potential protecting role of resveratrol (RES). Methods: Four sets of Balb/c mice were created: a diabetes mellitus (DM) group (streptozotocin (STZ) 55 mg/kg, i.p.], a control group administered buffer, a RES group [RES, 50 mg/kg, i.p.), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Tis report discovered that Rg1 treatment on DM mice advanced the mice's weight, infammatory response and promote the secretion of infammatory factors, such as TF, the infammatory biomarker, which would be activated through the CXCL16/ ox-LDL pathway in β-cell [36,37]. CXCL16, a special chemokine, can combine with immune cells to drive into the infammatory part, and some can internalize ox-LDL [38,39]. Tis study observed the colocalized expression of INSR or CD45 with CXCL16 by immunofuorescence and found there was infammatory in the pancreas of T1D mice, and Rg1 treatment could signifcantly improve this situation.…”
Section: Discussionmentioning
confidence: 99%
“…Tis report discovered that Rg1 treatment on DM mice advanced the mice's weight, infammatory response and promote the secretion of infammatory factors, such as TF, the infammatory biomarker, which would be activated through the CXCL16/ ox-LDL pathway in β-cell [36,37]. CXCL16, a special chemokine, can combine with immune cells to drive into the infammatory part, and some can internalize ox-LDL [38,39]. Tis study observed the colocalized expression of INSR or CD45 with CXCL16 by immunofuorescence and found there was infammatory in the pancreas of T1D mice, and Rg1 treatment could signifcantly improve this situation.…”
Section: Discussionmentioning
confidence: 99%